2014
DOI: 10.5958/2231-6701.2014.01216.0
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Soil and Nutrient Management Practices on Soil Properties and Additive Soil Quality Indices in SAT Alfisols

Abstract: A long term experiment was conducted for 11 years to study the effects of soil and nutrient management practices on soil fertility and additive soil quality indices in rainfed Alfisol, at Hyderabad, India. The treatments were comprised of conventional tillage (CT) and minimum tillage (MT) as main factors, sorghum stover (dry) @ 2 t/ha (SS), fresh gliricidia loppings @ 2 t/ha (GL) and no residue (NR) application on surface as sub-treatments and N levels @ 0, 30, 60 and 90 kg N/ ha as sub-sub treatments in casto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…To determine the carbon content in the extract, an aliquot of the filtered extract was digested with potassium persulfate/sulfuric acid; the evolved CO 2 was trapped in an NaOH solution and quantified titrimetrically in the presence of BaCl 2 . The microbial biomass C was determined by calculating the difference of carbon content in fumigated and unfumigated soil using a correction factor (K c ) of 0.25 (Sharma et al 2014;Debnath et al 2015).…”
Section: Soil Microbial and Biochemical Indicatorsmentioning
confidence: 99%
“…To determine the carbon content in the extract, an aliquot of the filtered extract was digested with potassium persulfate/sulfuric acid; the evolved CO 2 was trapped in an NaOH solution and quantified titrimetrically in the presence of BaCl 2 . The microbial biomass C was determined by calculating the difference of carbon content in fumigated and unfumigated soil using a correction factor (K c ) of 0.25 (Sharma et al 2014;Debnath et al 2015).…”
Section: Soil Microbial and Biochemical Indicatorsmentioning
confidence: 99%
“…Gabhane et al, (2014) showed that integrated application of FYM @ 10 t ha -1 along with 50% recommended dose of fertilizers through chemical fertilizers was beneficial in improving soil quality index and sustaining the cotton productivity in rainfed vertisols under semiarid region of Maharashtra. Sharma et al, (2014) observed the significant linear relationships between soil quality indices (physical, physico-chemical, chemical properties) and crop yield (sorghum and castor). Shirale et al, (2014) reported that application of NPK+FYM under Soyabean-Safflower system was significantly superior over rest of the treatments in respect of grain yield, yield equivalent, B:C ratio and buildup of soil fertility.…”
Section: Available Potassiummentioning
confidence: 88%
“…Upadhayay et al, (2013) noticed that the treatments involving incorporation of organic matter and residue recycling, improved the soil physical conditions by increasing in-situ infiltration rate, hydraulic conductivity, porosity and decreasing particle/ bulk density in all the cropping systems. Sharma (2014) observed that continuous application of organic alone or in combination with inorganic fertilizer significantly increased the hydraulic conductivity of the soil. The increase in hydraulic conductivity might be due to addition of organic matter which in turn increased porosity of soil.…”
Section: Hydraulic Conductivitymentioning
confidence: 98%
“…Based on a long-term study (2005-2012) by Sharma et al 27 in sorghumcowpea system in rainfed Alfisol, it was found that the surface application of sorghum residue @ 6 and 4 tonne ha -1 increased grain yield by 21% and 16% respectively, compared to control (no residue), whereas the corresponding increase in cowpea yield was 50% and 60% respectively. Similarly, application of dry sorghum residue (2 tonne ha -1 ) and fresh gliricidia loppings (2 tonne ha -1 ) showed significant increase in organic carbon by 6.28% and 3.7% respectively, over no residue application 28 . Besides these, other important soil properties such as available N, available K, exchangeable Mg, available S, microbial biomass carbon (MBC), dehydrogenase activity (DHA), labile carbon (LC), bulk density (BD) and mean weight diameter (MWD) of soil aggregates were also significantly improved.…”
Section: Crop Residuesmentioning
confidence: 96%